2021
DOI: 10.1609/aaai.v35i14.17499
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Neural Model for Biomedical Entity Linking

Abstract: Biomedical entity linking aims to map biomedical mentions, such as diseases and drugs, to standard entities in a given knowledge base. The specific challenge in this context is that the same biomedical entity can have a wide range of names, including synonyms, morphological variations, and names with different word orderings. Recently, BERT-based methods have advanced the state-of-the-art by allowing for rich representations of word sequences. However, they often have hundreds of millions of parameters and req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, efficiency and scalability are essential for real-time and large-scale applications. Although Lai et al [84] and Chen et al [86] aimed to determine how to improve the efficiency of EL tasks, they did not perform tests on large datasets. Therefore, an essential direction for future research is to investigate the design of systems that substantially improve the efficiency and scalability of BM-EL systems while maintaining high accuracy and precision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, efficiency and scalability are essential for real-time and large-scale applications. Although Lai et al [84] and Chen et al [86] aimed to determine how to improve the efficiency of EL tasks, they did not perform tests on large datasets. Therefore, an essential direction for future research is to investigate the design of systems that substantially improve the efficiency and scalability of BM-EL systems while maintaining high accuracy and precision.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [86] also used CNN as the backbone network of the model to significantly reduce the model parameters. They further introduced more features into the embedding representation of mention and entity to improve the model performance.…”
Section: Improvements On Model Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Other biomedical studies can be found for EL. Chen, Wang, et al (2020) and Chen, Varoquaux, et al (2020) proposed a lightweight neural method for biomedical EL. The method only needs some of the parameters of the BERT model.…”
Section: Other Studiesmentioning
confidence: 99%